2004
DOI: 10.1105/tpc.104.022038
|View full text |Cite
|
Sign up to set email alerts
|

VASCULAR ASSOCIATED DEATH1, a Novel GRAM Domain–Containing Protein, Is a Regulator of Cell Death and Defense Responses in Vascular Tissues

Abstract: The hypersensitive response (HR) is a programmed cell death that is commonly associated with plant disease resistance. A novel lesion mimic mutant, vad1 (for vascular associated death1), that exhibits light conditional appearance of propagative HR-like lesions along the vascular system was identified. Lesion formation is associated with expression of defense genes, production of high levels of salicylic acid (SA), and increased resistance to virulent and avirulent strains of Pseudomonas syringae pv tomato. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
126
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 76 publications
(92 reference statements)
9
126
0
4
Order By: Relevance
“…Like Meng et al (2009), we found that spontaneous cell death and the formation of lesions on leaves of mips1 mutants paralleled the progressive decline of myo-inositol in mips1 mutants throughout development (Figure 8) and can be rescued by myo-inositol supplementation (see Supplemental Figure 6 online). Overall, the mips1 mutants share characteristics with other lesion-mimic mutants (Lorrain et al, 2003) in that light potentiates the development of lesions (Bowling et al, 1997;Jambunathan et al, 2001;Lorrain et al, 2004), and the overall gene expression pattern is similar to lesion mimics as well as plants exposed to abiotic stress (Meng et al, 2009). Meng et al (2009) also noted a dependence on salicyclic acid (SA) synthesis for lesion formation in mips1 mutants and a reduction in the galactinol levels, which requires myo-inositol for synthesis and has been speculated to function as a general ROS scavenger.…”
Section: Myo-inositol Ptdins Ceramide and Cell Deathmentioning
confidence: 99%
“…Like Meng et al (2009), we found that spontaneous cell death and the formation of lesions on leaves of mips1 mutants paralleled the progressive decline of myo-inositol in mips1 mutants throughout development (Figure 8) and can be rescued by myo-inositol supplementation (see Supplemental Figure 6 online). Overall, the mips1 mutants share characteristics with other lesion-mimic mutants (Lorrain et al, 2003) in that light potentiates the development of lesions (Bowling et al, 1997;Jambunathan et al, 2001;Lorrain et al, 2004), and the overall gene expression pattern is similar to lesion mimics as well as plants exposed to abiotic stress (Meng et al, 2009). Meng et al (2009) also noted a dependence on salicyclic acid (SA) synthesis for lesion formation in mips1 mutants and a reduction in the galactinol levels, which requires myo-inositol for synthesis and has been speculated to function as a general ROS scavenger.…”
Section: Myo-inositol Ptdins Ceramide and Cell Deathmentioning
confidence: 99%
“…CYCA2;1 (Burssens et al, 2000), SCL3 (Ckurshumova et al, 2009), CESA2 (Beeckman et al, 2002)] and those with a proposed role in vascular development [e.g. VAN3 (SFC) (Deyholos et al, 2000;Koizumi et al, 2000), VAD1 (Lorrain et al, 2004), VND4 (Kubo et al, 2005)] or auxin response [e.g. ARF2 (Li et al, 2004), AXR3 (IAA17) (Rouse et al, 1998), HAT2 (Sawa et al, 2002)].…”
Section: Regulatory Elements In Preprocambial Cell State Acquisitionmentioning
confidence: 99%
“…Plant inoculations and in planta bacterial growth analysis were performed essentially as described previously (Lorrain et al, 2004) using six to eight replicate plants per experiment. For the determination of disease symptoms and in planta bacterial growth, we used an inoculum of 10 5 cfu/mL for Pst DC3000 and of 2 3 10 5 cfu/mL for Pst DC3000 (avrRpt2).…”
Section: Bacterial Strains Plant Inoculation Procedures and Bacterimentioning
confidence: 99%